Functional Neuroimaging in Rodents Using Cerebral Blood Flow SPECT - Oelschlegel, Anja M.; Goldschmidt, Jürgen (Frontiers in Physics, 2020)
The brain-wide activation patterns that underlie, generate and change the behavioral outputs in rodents, the main animal models in biomedical research, are difficult to assess in vivo. The standard tool for whole-brain imaging of spatiotemporal activation patterns in rodents is BOLD fMRI, but the technique requires the animals to be immobilized inside the scanners. One of the few methods that can provide in vivo images of brain-wide patterns of neural activity from unrestrained animals outside scanner environments is single-photon emission computed tomography (SPECT) imaging of cerebral blood flow (CBF). During ongoing behavior animals are intravenously injected with 99mTc-HMPAO (99m-technetium hexamethylene propyleneamine oxime), a lipophilic tracer that, after accumulation in the brain in a flow-dependent manner, is rapidly converted to a hydrophilic compound that remains trapped in the brain and shows no redistribution. The 99mTc brain distribution, reflecting the average blood flow during the time of injection, can be read out in the anesthetized animal after injection. Similar in rationale to 18F-2-fluoro-2-deoxy-glucose (18F-FDG) positron emission tomography (PET) 99mTc-HMPAO SPECT provides static images of spatial patterns of neural activity from awake behaving rodents, but the spatial resolution can be higher and the stimulation times substantially shorter. In this review we present an overview about the underlying rationales and principles of functional CBF SPECT imaging in rodents, give a short summary of the experimental procedures and discuss the advantages, drawbacks and perspectives of the technique within the framework of methods for imaging brain-wide activation patterns in awake behaving rodents.